Polymer materials for energy and electronic applications. - Peng, Huisheng (Academic Press, 2017)
Polymer Materials for Energy and Electronic Applications is among the first books to systematically describe the recent developments in polymer materials and their electronic applications. It covers the synthesis, structures, and properties of polymers, along with their composites. In addition, the book introduces, and describes, four main kinds of electronic devices based on polymers, including energy harvesting devices, energy storage devices, light-emitting devices, and electrically driving sensors. Stretchable and wearable electronics based on polymers are a particular focus and main achievement of the book that concludes with the future developments and challenges of electronic polymers and devices. * Provides a basic understanding on the structure and morphology of polymers and their electronic properties and applications. * Highlights the current applications of conducting polymers on energy harvesting and storage. * Introduces the emerging flexible and stretchable electronic devices. * Adds a new family of fiber-shaped electronic devices.- Resumé vydavatele
Keywords: polymery; elektrické vlastnosti materiálů; akumulace energie; polymers; electric properties of materials; energy storage; monografie; elektronické knihy; monographs; electronic books